Equipment‐based route index of inherent safety. (12th November 2019) - Athar, Muhammad; Shariff, Azmi M.; Buang, Azizul; Hermansyah, Heri
Abstract: Process safety concept is used to deal with accident scenarios occurring as a result of loss containment. There are four tactics of process safety, and due to superior characteristics, the inherent theme is given priority at the preliminary design stage. In open literature, various methods have been proposed to identify the inherent safety level, and among these indexing methods are typically used. The reported indices have a shortcoming that these have not considered equipment characteristics for inherent safety assessment. Therefore, a new indexing method is proposed in this article to improve the quantification of inherent safety level. This index incorporates process, chemical, and equipment aspects to define the safety level of various process routes via the relative ranking. The proposed index has been tested on process routes to produce methyl methacrylate, which confirms the applicability of this index. The index would enable the practitioners to thoroughly analyze and compare the process routes to identify the inherently safer route.